2014
DOI: 10.2355/isijinternational.54.2900
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Atom Re-Distribution during Quenching and Partitioning

Abstract: Quenched and Partitioned (Q&P) steels have been shown in previous literature to exhibit attractive mechanical properties due to austenite and martensite present in the microstructure. However, questions have remained regarding the mechanisms at work during the partition step. In this work, x-ray diffraction and atom probe tomography were utilized to gain insights into phenomena that occur (such as carbon partitioning from martensite to austenite, carbon atom clustering/dislocation trapping, and carbide formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 8 publications
6
16
0
Order By: Relevance
“…Carbon enrichment in austenite was shown to be the result of the competition between the direct partitioning process and the carbide-free bainitic transformation. They also showed that a significant fraction of carbon remains trapped in martensite, supporting the conclusions of Thomas et al [15].…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…Carbon enrichment in austenite was shown to be the result of the competition between the direct partitioning process and the carbide-free bainitic transformation. They also showed that a significant fraction of carbon remains trapped in martensite, supporting the conclusions of Thomas et al [15].…”
Section: Introductionsupporting
confidence: 79%
“…Their observations are sustained with an original reassessed thermo-kinetic model. Carbon clustering in martensite has also been reported by Thomas et al [15] in a highly-alloyed system. Even if the nature of the carbide remains the bone of contention, all these recent studies lead to the conclusion that a certain fraction of carbon must also be trapped in recovered martensitic laths, preventing a complete carbon partitioning between martensite and austenite, thus limiting austenite carbon enrichment.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…Predicting the development of the martensite volume fraction is of interest, for example, in the case of quenched and partitioned steels, where the amount of austenite remaining at the quench stop temperature is an important parameter in process design. [3][4][5] For plain iron -carbon alloys, Koistinen and Marburger (K-M) 6) showed that the transformation of austenite to mar-…”
Section: Introductionmentioning
confidence: 99%